Sufficient conditions for oscillation of solutions of first order neutral delay impulsive differential equations with constant coefficients - Dimitrova, M.B.; Donev, V.I. (Нелінійні коливання, 2010)
This paper is dealing with the oscillatory properties of first order neutral delay impulsive differential equations and the corresponding inequalities with constant coefficients. The established sufficient conditions ensure oscillation of every solution of this type of the equations. Розглянуто осциляцiйнi властивостi розв’язкiв диференцiальних рiвнянь першого порядку зi сталими коефiцiєнтами та нейтральним запiзненням iмпульсної дiї та вiдповiдних до них нерiвностей. Знайденi умови є достатнiми для того, щоб кожний розв’язок рiвняння такого типу був осциляцiйним.